Peran Profitabilitas Memediasi Kinerja Lingkungan, Penghindaran Pajak, Keputusan Investasi terhadap Nilai Perusahaan Sektor Pertambangan - Ruly Firniza; Munawaroh; Dhistianti Mei Rahmawantari (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
The research is to analyze the causes of Environmental Performance, Tax Avoidance, Investment Decisions factors on company value with the role of profitability as a mediating. The research method used in this study is a quantitative descriptive method. Data analysis in this study uses panel data regression with a population of 81 (eighty one) observations of Mining Sector Companies listed on the Indonesia Stock Exchange. Companies that meet the requirements in this study are 20 (twenty) mining sector companies. Then the analysis method used in path analysis. The results of 1) Environmental performance has no effect on company value in mining sector companies; 2) Tax avoidance has no significant effect on company value in mining sector; 3) Investment decisions have no effect on company value in mining sector companies; 4) Profitability cannot mediate environmental performance's effect on the value of mining sector companies; 5) Profitability can moderate investment decisions to affect the value of companies in the mining sector; 6) Profitability mediates investment decisions affecting the value of companies in the mining sector.